Teacher Guidance and Counseling Strategies in Helping Grade 1 Students Adjust to the School Environment - Siti Rahmah Harahap; Miftahul Jannah; Rostina Rangkuti; Mhd. Daswar; Anwar Nasution; Nurmia Hasibuan (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to describe and analyze the strategies employed by Guidance and Counseling teachers to facilitate the school adjustment of first-grade students, as well as to explore the underlying factors contributing to the effectiveness of these approaches. The transition from the family environment to primary school often triggers intense affective barriers, such as classroom tantrums and separation anxiety in young learners. To investigate this phenomenon, this study employed a qualitative approach with a field-based case study design. Data were gathered through a triad of qualitative techniques: passive participant observation, semi-structured interviews with BP teachers, first-grade homeroom teachers, and parents, alongside comprehensive documentation reviews. Data analysis followed an interactive framework including data condensation, data display, and conclusion drawing. The findings reveal that the primary effective strategy is a play-based guidance framework, executed by transforming the counseling room into a child-friendly "Transition Corner." The effectiveness of this strategy is highly driven by a structured tri-party collaborative model between BP teachers, homeroom educators, and parents, which successfully synchronizes psychological support between home and school. Ultimately, this study implies the critical need to reposition the role of BP teachers at the primary level as transition curriculum strategists to mitigate early academic trauma and foster sustainable school readiness.